2019
DOI: 10.1016/j.gaitpost.2019.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Centre of mass control is reduced in older people when descending stairs at an increased riser height

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Therefore, it is expected that both groups would be at an increased fall risk, and by the same mechanisms, on stairs with inconsistent rise heights. However, it is likely that the consequences will be more severe for the older adults who may not be able to control their CoM as well as younger adults (Foster et al, 2019) as they do not have adequate strength reserves to recover should they lose balance (Pijnappels et al, 2008;Reeves et al, 2008). It previously been reported that poor lighting conditions (Kim, 2009;Thomas et al, 2020) and dual-tasking such as talking on the phone (Di Giulio et al, 2020) can further compromise Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is expected that both groups would be at an increased fall risk, and by the same mechanisms, on stairs with inconsistent rise heights. However, it is likely that the consequences will be more severe for the older adults who may not be able to control their CoM as well as younger adults (Foster et al, 2019) as they do not have adequate strength reserves to recover should they lose balance (Pijnappels et al, 2008;Reeves et al, 2008). It previously been reported that poor lighting conditions (Kim, 2009;Thomas et al, 2020) and dual-tasking such as talking on the phone (Di Giulio et al, 2020) can further compromise Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Although stair fall risk is notably heightened for an older adult largely due to age related factors such as reduced vision or musculoskeletal function [2], stairs falls occur across the lifespan [3] and are a broad societal issue. Many factors can affect stair fall risk including frailty, risky behaviour (such as carrying objects on stairs) and poor vision [2], but several previous reports demonstrate the importance of the built environment and in particular stair dimensions in dynamic balance control and the circumstance of stair falls [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Most research on this parameter derives from biomechanics analysis in runners, but it is also known that older people for example display a lower landing acceleration, e.g., while descending stairs. This is believed to be a compensation mechanism for the poorer balance control, which is achieved by increased "stiffening" at knee and ankle of the stance leg [17]. We believe that this phenomenon may underlie the particular walking pattern, which in few of our patients results in a clinically evident cautious-seeming, heel-based gait, as if they were "walking on eggshells".…”
Section: Discussionmentioning
confidence: 74%